Experimental investigation of CO2-enhanced coalbed methane recovery using large intact coal cores - Zhiming Fang; Chenlong Yang; Shaicheng Shen (Journal of CO2 Utilization)
The integration of CO₂-enhanced coalbed methane recovery (CO₂-ECBM) with carbon sequestration offers a dual solution for energy security and climate mitigation. However, existing laboratory studies predominantly rely on crushed or small-scale coal samples, which inadequately replicate the structural heterogeneity and scale-dependent dynamics of in-situ coal seams. This study addresses this critical gap by conducting CO₂-ECBM experiments on large intact anthracite cores (104 mm diameter × 301.5 mm length) under simulated reservoir conditions. A bespoke apparatus enabled multi-phase experiments, including CH₄ adsorption equilibrium, pressure-depletion desorption, and CO₂ injection, with real-time monitoring of produced gas composition and flow rate. Results demonstrate that CO₂ injection significantly enhances CH₄ recovery, achieving a 212 % improvement in recovery rate during the initial flooding stage (2.0 MPa CO2 injection). However, progressive permeability reduction (87.5 % decline from CH₄-saturated state) and CH₄ reserve depletion led to diminishing returns in later stages. Rapid CO₂ breakthrough (2.12 h post-injection) and preferential flow pathways were observed, accompanied by dynamic gas composition shifts. The study highlights the necessity of large-scale experimentation to capture fracture networks, adsorption dynamic, swelling-induced permeability reduction, and displacement efficiency inherent to field-scale operations. These findings provide critical insights for optimizing CO₂ injection strategies and mitigating permeability damage in practical CO₂-ECBM applications.